2021
DOI: 10.1186/s12889-021-10329-3
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of depression, anxiety, and stress and its relating factors during COVID-19 pandemic in Iran

Abstract: Background The COVID-19 (SARS-CoV-2) is an emerging epidemic caused by the new Coronavirus. It has affected more than 200 countries, infected 5,939,234 people, and killed 367,255 in the world until 1 June 2020. While the disease epidemic could affect population mental health, this study aimed to investigate stress, anxiety, and depression during the Corona pandemic in Iran. Methods An online survey was designed using the depression, anxiety, and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
90
6
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(110 citation statements)
references
References 18 publications
10
90
6
4
Order By: Relevance
“…Research has shown that epidemics can cause severe and variable psychological effects on people [8,9]. The growing literature on COVID-19 has already shown that the pandemic and accompanying measures have had a profound effect on-besides health issues-all aspects of society, including mental health [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that epidemics can cause severe and variable psychological effects on people [8,9]. The growing literature on COVID-19 has already shown that the pandemic and accompanying measures have had a profound effect on-besides health issues-all aspects of society, including mental health [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Several mental health studies on COVID-19 found associations between demographic characteristics and mental health. It seems that younger people (< 30 years, inclusive of students [19,20]) [13,[21][22][23][24][25]; women [9,13,19,20,22,26]; healthcare workers [13,21]; unemployed people [19]; adults who have children [27,28]; people living in rural areas [29]; those having cancer or chronic diseases [23]; those living with family member at high risk for COVID-19 [9]; and those living alone [23] have the highest risk to develop mental health problems such as anxiety or depression during the COVID-19 crisis.…”
Section: Introductionmentioning
confidence: 99%
“… Meng et al, 2020 DASS-21 1498 participants 18 to 28 in Iran, April 2020 31.8% − 10.70% (− 14.88% to − 6.18%) χ 2 (1) = 19.99, p < 0.0001 N.A. Khademian et al ( 2021 ) DASS-21 10,754 individuals from the general population in Iran, March 1–9, 2020 40.4% − 19.30% (− 22.85% to − 15.30%) χ 2 (1) = 71.00, p < 0.0001 Negative Moghanibashi-Mansourieh ( 2020 ) Distress Kessler-6 369 adults in China, Feb 20–21, 2020 6.15% 8.62% (4.48% to 12.65%) χ 2 (1) = 15.73, p = 0.0001 N.S. Zhang et al ( 2020b ) Kessler-10 500 adults in Italy, April 10–13, 2020 18.6% − 3.83% (− 0.87% to 8.49%) χ 2 (1) = 2.559, p = 0.110 Negative Moccia et al ( 2020 ) Kessler-6 1599 adults in China, Feb 1–4, 2020 Mean (SD), 7.7 (± 7.7) 0.62 (− 0.11 to 1.35) df = 2071, p = 0.098 Negative Wang et al ( 2020 ) Kessler-6 2032 adults in the USA, late April 2020 27.7% − 12.93% (− 16.45% to − 8.97%) χ 2 (1) = 34.03, p < 0.001 N.A.…”
Section: Resultsmentioning
confidence: 98%
“… Liu et al ( 2020 ) DASS-21 1498 participants 18 to 28 in Iran, April 2020 34.7% − 12.76% (− 17.02% to − 8.17%) χ 2 (1) = 27.18, p < 0.0001 N.A. Khademian et al ( 2021 ) Anxiety GAD-2 3088 adults in 32 provinces of China, Feb 20–27, 2020 13.2% 7.9% (4.25% to 11.96%) χ 2 (1) = 20.980, p < 0.001 N.S. Song et al ( 2020 ) GAD-2 3480 adults in Spain, March 21–27, 2020 21.6% 0.50% (− 3.62% to 4.21%) χ 2 (1) = 0.062, p = 0.804 Negative González-Sanguino et al ( 2020 ) GAD-7 103 adults in China, Feb 10–28, 2020 22.3% − 1.20% (− 10.79% to 6.78%) χ 2 (1) = 0.07, p = 0.788 N.A.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, other factors could contribute to these symptoms such as overall stressor of experiencing a pandemic, among others. 41 This would require additional history beyond the scope of this study. Lastly, being a cross sectional study, it was not possible to establish causality between explanatory and outcome variables; nevertheless, our findings may contribute to the understanding of the mental health effects on the population during a COVID-19 outbreak.…”
Section: Strengths and Limitationsmentioning
confidence: 99%